Conventional and unconventional monetary policies: Effects on the Finnish housing market - Signe Rosenberg (Baltic Journal of Economics, 2020)
This paper investigates how different types of monetary policy have affected house prices in Finland, a small euro area economy that has experienced pronounced business cycles over time. The analyses are carried out using the Bayesian structural vector autoregressive approach. Monetary policy interest rate shocks and balance sheet shocks are identified using zero and sign restrictions. The results reveal that both a policy interest rate shock and a balance sheet shock have a positive and temporary impact on house prices in Finland, with the response to a balance sheet shock being smaller and fading out faster. The peak of the effect of a policy rate shock on house prices in Finland arrives faster than in the whole euro area but the magnitudes of the peak impact are similar. The effect of a balance sheet shock on house prices is not notably different in Finland to what it is in the whole euro area.
Keywords: C32; E30; E42; E52; R31; 330; BSVAR; euro area; house prices; Monetary policy; zero and sign restrictions